Superior Strategic Markowitz Portfolio in Weak form Inefficient Jakarta Stock Exchange - Sholehuddin, Rohmat Agung; Damayanti, Sylviana Maya (Journal of Business and Management, 2016)
Abstract. Capital market has become a regular investment alternative for investors. The existence of capital market provides the chance for investors to maximize their assets. However, capital market has its own risk characteristic. Related to the chance of risk and return, Jakarta Stock Exchange is available to provide the high possibility of earning return, respectively it also provides the high possibility of risk, as it is inefficient of weak-form market efficiency. Investors need to arrange the excellent investment strategy to prepare the investment action in Indonesia.Regarding to the availability of risk and return, investors have their own preference of investment. In general, investors are categorized as aggressive, moderate, and conservative risk profiled. The aggressive investors tend to select more risky assets in order to earn more return though they have to face the higher possibility of risk. The moderate investors tend to select the assets with fair possibility risk and return. And the conservative investors tend to select the assets that provide the lower risk though it will reduce the chance of gaining more return. To incorporate with this condition, investors need the excellent portfolio strategies for their investment. This study is using combined means-variance Markowitz portfolio combined with Merrill Lynch asset allocation for projected portfolio 2015 to 2018. And the results are efficient. The additional asset and fixed income asset included effectively reduce and diversify the potential risk.Â Keywords: Capital market, weak-from inefficiency, investor risk tolerance, asset allocation, Markowitz portfolio